C-reactive protein and modified computed tomography severity index in assessing severity of acute pancreatitis - Lahan , Kashyapi; Sonowal, Naruttam; Anju Barhoi Teli; Bhuyan, Rupak; Himavathy K Gara; Vanamali, Dharma Rao (Asian Journal of Medical Sciences, 2023)
Background: The mortality and morbidity associated with acute pancreatitis (AP) demands timely management and prediction of disease progression and clinical outcome. Multifactorial scoring systems shall facilitate risk stratification and prognostic assessment in AP. Aims and Objectives: The aim of the study was (i) to assess C-reactive protein (CRP) levels and modified computed tomography severity index (mCTSI) in AP patients and their association with the clinical outcome and (ii) to determine the correlation between CRP levels and mCTSI scores in AP. Materials and Methods: This cross-sectional, hospital-based study comprised 90 patients diagnosed with AP. Data collection included sociodemographic information, clinical presentation, and CRP estimation. The mCTSI score was estimated by axial slices contrast-enhanced computed tomography of abdomen and was used to assess the severity of AP. Categorical data were analyzed by Chi-square test and Pearson’s coefficient was estimated to determine the correlation between CRP levels and mCTSI score. P<0.05 was adopted as level of significance. Results: The study comprised 81 males (90%) and 9 females (10%). The mean age of the patients was 36.94±9.19 years, with majority in age group of 31–40 years (40%). Alcohol consumption (>50 g/day) was the commonest risk factor in 82.22% (n=74) patients, followed by hypertriglyceridemia in 13.33% (n=12) patients. Pain in abdomen was the most common presentation in 96.67% (n=87) patients, followed by vomiting 57.78% (n=52) patients. Majority of patients [82.22% (n=74)] had CRP levels of 10–21 mg/dL. Mild, moderate, and severe mCTSI scores were obtained in 17.78%, 66.67%, and 15.55% patients, respectively. There is a significant positive correlation between CRP values and mCTSI scores with r=0.3008 (P=0.003). Conclusion: CRP level had significant positive correlation with mCTSI scores in AP. Higher values of CRP and severe mCTSI scores had worse clinical outcome in AP.